Evaluating the impact of a coach educational intervention on relative energy deficiency in sport: A pilot study - Hamer, J.; Desbrow, B.; Irwin, C.; Shaw, G.; Disher, A.; Alexiou, H. (International Journal of Sports Science & Coaching, 2024)
Athletes undertaking large training volumes are often exposed to periods of low energy availability (LEA) and consequently are at risk of developing Relative Energy Deficiency in Sport (REDs). Swim coaches play a key role in moderating this risk in developing swimmers. This study aimed to evaluate swimming coaches` perceptions of LEA/REDs education intervention developed using the Public Health Nutrition Bicycle Framework and underpinned by the professional tools of problem analysis, system mapping and training development. Data was collected in two phases: 1) an immediate post-workshop evaluation survey (process evaluation), and 2) a delayed (6 weeks) post workshop informal roundtable (impact/outcome evaluation). The process evaluation was conducted inductively using three questions (a mix of categorical and open-ended questions). The impact/outcome evaluation was deductive, with the Capability, Opportunity and Motivation Model of Behaviour Change (COM-B) used to evaluate coaches` likelihood of implementing new learnings after attending the workshop. Twenty-one coaches attended the workshop, and fourteen completed the post workshop survey. The process evaluation findings indicated that coaches found numerous aspects of the workshop valuable, including the case study approach, resources for consolidation of learning and discussions around the challenges they may experience when managing athletes at risk. The impact/outcome evaluation identified eleven facilitatory and four inhibitory themes based on the COM-B model. Coaches reported an enhanced understanding and knowledge of REDs but lacked the physical and psychological capability to apply new knowledge and/or desired behaviours in practice. The integration of applied frameworks and research and development specialists in coach education may be important when addressing sensitive and complex topics in sport to support the effective dissemination of knowledge into applied contexts. This requires effective partnerships between researchers, national sporting organisations and experts in design and development to strengthen the integrity and applicability of future coach education initiatives.